Single-nuclei and bulk-tissue gene-expression analysis of pheochromocytoma and paraganglioma links disease subtypes with tumor microenvironment - Zethoven, Magnus; Martelotto, Luciano; Pattison, Andrew; Bowen, Blake; Balachander, Shiva; Flynn, Aidan; Rossello, Fernando J; Hogg, Annette; Miller, Julie A; Frysak, Zdenek; Grimmond, Sean; Fishbein, Lauren; et al. (Nature communications, 2022)
Pheochromocytomas (PC) and paragangliomas (PG) are rare neuroendocrine tumors associated with autonomic nerves. Here we use single-nuclei RNA-seq and bulk-tissue gene-expression data to characterize the cellular composition of PCPG and normal adrenal tissues, refine tumor gene-expression subtypes and make clinical and genotypic associations. We confirm seven PCPG gene-expression subtypes with significant genotype and clinical associations. Tumors with mutations in VHL, SDH-encoding genes (SDHx) or MAML3-fusions are characterized by hypoxia-inducible factor signaling and neoangiogenesis. PCPG have few infiltrating lymphocytes but abundant macrophages. While neoplastic cells transcriptionally resemble mature chromaffin cells, early chromaffin and neuroblast markers are also features of some PCPG subtypes. The gene-expression profile of metastatic SDHx-related PCPG indicates these tumors have elevated cellular proliferation and a lower number of non-neoplastic Schwann-cell-like cells, while GPR139 is a potential theranostic target. Our findings therefore clarify the diverse transcriptional programs and cellular composition of PCPG and identify biomarkers of potential clinical significance.
Keywords: feochromocytom; sukcinátdehydrogenasa; nádory nadledvin; nádorové mikroprostředí; Pheochromocytoma; Tumor Microenvironment; Paraganglioma; Adrenal Gland Neoplasms; paragangliom; Succinate Dehydrogenase; Humans; lidé